2010
DOI: 10.3892/or_00000813
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-regulated expression of oncogenes and tumor suppressor genes in the cisplatin-inhibited growth of K562 cells

Abstract: Abstract.To explore the mechanism of apoptosis induced by cisplatin, the expression of microRNAs (miRNAs) and regulating genes in K562 cells was analyzed using reverse transcription PCR, quantitative real-time PCR and enzymelinked immunosorbent assays. Our results showed that miR-16, miR-34a-c, miR-17-5p and miR-125 were upregulated, and their associated oncogenes (BCL2, E2F1 and E2F3, respectively) were down-regulated after cisplatin treatment. We also showed that miR-106 and miR-150 were down-regulated while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…miR-150 has been previously reported to be differentially expressed in various hematopoietic cell lineages of a specific developmental stage or characteristically up-or downregulated in various types of hematopoietic malignancies, including leukemia, lymphoma and myelodysplastic syndrome (14). In chronic myeloid leukemia (CML), miR-150 has been demonstrated to be involved in the mechanism of apoptosis induced by cisplatin in the human CML cell line, K562 (18). Xie et al (18)demonstrated a negative correlation between the expression levels of miR-150 and p53 following treatment of K562 cells with cisplatin, indicating that cisplatin induced apoptosis in the K562 cells by inhibiting miR-150 expression, which then upregulated p53 expression.…”
Section: Role Of Microrna-150 In Solid Tumors (Review)mentioning
confidence: 99%
“…miR-150 has been previously reported to be differentially expressed in various hematopoietic cell lineages of a specific developmental stage or characteristically up-or downregulated in various types of hematopoietic malignancies, including leukemia, lymphoma and myelodysplastic syndrome (14). In chronic myeloid leukemia (CML), miR-150 has been demonstrated to be involved in the mechanism of apoptosis induced by cisplatin in the human CML cell line, K562 (18). Xie et al (18)demonstrated a negative correlation between the expression levels of miR-150 and p53 following treatment of K562 cells with cisplatin, indicating that cisplatin induced apoptosis in the K562 cells by inhibiting miR-150 expression, which then upregulated p53 expression.…”
Section: Role Of Microrna-150 In Solid Tumors (Review)mentioning
confidence: 99%
“…Studies have revealed that miRNA may affect a multitude of target genes and that one target gene may be regulated by multiple miRNA molecules (17)(18)(19). The miR-17-92 cluster has been considered to be the most effective carcinogenic miRNA, and hundreds of target genes of this cluster have been reported (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-302 downregulated TP63, one of its target genes, and inhibition of miR-302 upregulated TP63 in germ cell tumors [32]. Overexpression of miR-17-5p downregulated E2F transcription factor 1 (E2F1), and inhibition of miR-17-5p upregulated E2F1 in K562 cells [38]. Glucose energy and metabolism are crucial for embryonic stem cells, induced pluripotent stem cells, and germ cells [11][12][13], and a variety of miRNAs play a role in the regulation of glucose metabolism in the pancreas, liver, brain, muscle, and adipose tissue [8,16].…”
Section: Regulation Of Glucose Phosphate Isomerase By Mirnamentioning
confidence: 99%